Dynamic control of robotic arm manipulation for education purpose - Mohd Razali, Muhammad Raziq Hudzaifah (2025)
Autonomous robots have been introduced to numerous industries in this era to aid with transportation, production, and simple task handling. Robotic arms are used in the manufacturing sector in the automobile, assembly, and lifting of heavy objects. However, we still need to learn how to operate and program the robotic arm in order to meet future demands. In real time, students can be exposed to various learning types through practical or physical simulations. Students must conduct educational study on the robotic arm for this assignment